Applying the Brocher Declaration to short-term experiences in global health in dental education - Rosenbaum, Edward; Lasker, Judith; Prasad, Shailendra; Shick, Elizabeth (Frontiers in Education, 2023)
It is estimated that 3.5 billion people are affected by oral health diseases globally, making it the most prevalent non-communicable disease. 1 Reducing the prevalence of such a widespread disease requires innovative solutions in public health workforce development. This may be accomplished by designing formative programs that take place during dental education to improve students' public health skillset. Experiences for dental students that focus on the burden of oral disease, population health and oral health promotion are common among dental schools and include both didactic and experiential learning programs carried out both locally and abroad. 2,3,4 Participating in global health activities is popular among dental students and fosters critical thinking when tackling global health problems. Known as Short-Term Experiences in Global Health (STEGHs), they usually involve short-term dental student and faculty travel for less than 3 weeks to a Low-or Middle-Income Country (LMICs) or any community outside of the dental school. One study conducted in 2016, showed that approximately 65% of US Dental Schools offer STEGHs to their students. 2 Developing a fit-for-purpose STEGH program involves several components that must come together harmoniously to ensure these programs are effective for both the participating students and the host community. 5 Another complicating factor is that there is little to no monitoring and standard setting for these programs, as no one professional entity holds legal